2016
DOI: 10.1001/jamaoncol.2016.0740
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Physical Activity by Type and Intensity With Digestive System Cancer Risk

Abstract: Importance Accumulating evidence indicates that common carcinogenic pathways may underlie digestive system cancers. Physical activity may influence these pathways, yet no previous study has evaluated the role of physical activity in overall digestive system cancer risk. Objective To examine the association between physical activity and digestive system cancer risk, accounting for amount, type (aerobic versus resistance), and intensity of physical activity. Design A prospective cohort study followed from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 37 publications
0
65
0
6
Order By: Relevance
“…For example, dietary components such as red and processed meat increase CRC risk whilst others such as whole grains and vegetables are associated with a reduced CRC risk . Other factors, which are associated with a Western lifestyle, such as smoking, high alcohol consumption, low physical activity overweight and obesity have likewise been shown to be associated with increased CRC risk.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dietary components such as red and processed meat increase CRC risk whilst others such as whole grains and vegetables are associated with a reduced CRC risk . Other factors, which are associated with a Western lifestyle, such as smoking, high alcohol consumption, low physical activity overweight and obesity have likewise been shown to be associated with increased CRC risk.…”
Section: Introductionmentioning
confidence: 99%
“…In modern world, PA is already seen as an important component of a healthy life 6 , with recent studies having demonstrated the effect of PA level in predicting mortality of patients suffering from chronic conditions 7,8 , the association of lower PA with mortality rates in elderly 9 or even finding out that the metabolic equivalent of task (MET -Metabolic Energy Requirement in hours/ week) was inversely associated with the risk of digestive tract cancers in men. 10 Considering the above mentioned facts, our question raises upon the adherence phenomenon and possible correlation between active individuals and their educational status on the prevalence of medicines use in a population of a young, lowincome, post conflict and developing country such as Kosova.…”
Section: Introductionmentioning
confidence: 99%
“…By type of physical activity, aerobic activities were calculated by including walking, stair climbing, jogging, running, bicycling, swimming, tennis, squash/racquetball, calisthenics/rowing and heavy outdoor work . Resistance training included weight lifting/weight machine . Details of the physical activity questionnaire can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Total physical activity was categorized into five groups (i.e., 0–8.9, 9–20.9, 21–41.9, 42–62.9 and 63+ MET‐hr/week). The cut‐offs were based on multiples of 3 MET‐hours per week, which corresponds to 1 hr per week of normal walking or approximately 25 min per week of jogging for easier interpretation . All multivariable models adjusted for the potential confounders including age at blood draw (continuous, years), race (White or non‐White), case–control status, smoking status (never, former or current), regular aspirin/NSAID use (yes or no), chronic diseases/conditions (0, 1, 2 or 3+) and dietary pattern (quintiles).…”
Section: Methodsmentioning
confidence: 99%